Environmental & architectural phenomenology. Vol. 30, issue 2 - (:unkn) unknown (Kansas State University. Architecture Department, 2019)
Besides “items of interest,” and “citations received,” this issue includes the following items: An “in memoriam” for phenomenological sociologist George Psathas, who died last November; “Book notes” on philosopher Dan Zahavi’s Phenomenology: The Basics; and naturalist Paul Krafel’s Roaming Upward; The third part of the late philosopher Henri Bortoft’s 1999 conference presentation on Goethean science; Sociologist Julia Bennett’s overview of her doctoral research relating to belonging among families who have lived in one English town for multiple generations; Environmental educator John Cameron’s continuing discussion of “lived interiority” via consideration of landscape character as understood by several well-known thinkers and writers; Australian artist and photograph Sue Michael’s introductory text and several works that were part of her recent painting and photography exhibit, “Settled Areas”; To mark EAP’s 30th year of publication, editor David Seamon’s discussion of current conceptual and methodological concerns relating to phenomenology as a philosophy and research approach; The issue ends with 23 definitions of phenomenology written by eminent phenomenological thinkers.
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals